2017
DOI: 10.1186/s13024-017-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased acetylation of Peroxiredoxin1 by HDAC6 inhibition leads to recovery of Aβ-induced impaired axonal transport

Abstract: BackgroundReduction or inhibition of histone deacetylase 6 (HDAC6) has been shown to rescue memory in mouse models of Alzheimer’s disease (AD) and is recently being considered a possible therapeutic strategy. However, the restoring mechanism of HDAC6 inhibition has not been fully understood.Methods and resultsHere, we found that an anti-oxidant protein Peroxdiredoxin1 (Prx1), a substrate of HDAC6, malfunctions in Aβ treated cells, the brains of 5xFAD AD model mice and AD patients. Malfunctioning Prx1, caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 54 publications
3
45
0
1
Order By: Relevance
“…The neuroprotective effects of HDAC6 inhibitors have been demonstrated in models of neurological disorders, including Alzheimer disease and Charcot-Marie-Tooth disease. [43][44][45] The neuroprotective effects of HDAC6 inhibitors in these models are associated with improved mitochondrial axonal transport and reduced oxidative damage. [43][44][45] We recently demonstrated that HDAC6 inhibitors prevent cisplatin-induced deficits in axonal mitochondrial transport in primary cultures of DRG neurons.…”
Section: Targeting Neuronal Mitochondrial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neuroprotective effects of HDAC6 inhibitors have been demonstrated in models of neurological disorders, including Alzheimer disease and Charcot-Marie-Tooth disease. [43][44][45] The neuroprotective effects of HDAC6 inhibitors in these models are associated with improved mitochondrial axonal transport and reduced oxidative damage. [43][44][45] We recently demonstrated that HDAC6 inhibitors prevent cisplatin-induced deficits in axonal mitochondrial transport in primary cultures of DRG neurons.…”
Section: Targeting Neuronal Mitochondrial Dysfunctionmentioning
confidence: 99%
“…[43][44][45] The neuroprotective effects of HDAC6 inhibitors in these models are associated with improved mitochondrial axonal transport and reduced oxidative damage. [43][44][45] We recently demonstrated that HDAC6 inhibitors prevent cisplatin-induced deficits in axonal mitochondrial transport in primary cultures of DRG neurons. 30 In vivo, the coadministration of an HDAC6 inhibitor with cisplatin prevented cisplatin-induced neuropathic pain.…”
Section: Targeting Neuronal Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the brain tissue from these mice revealed increased levels of BDNF and synaptic proteins, and enhanced cellular energetics associated with cognitive protection. Similar, restoration of axonal trafficking using antioxidants, by increasing the acetylation of anti-oxidant protein peroxdiredoxin1 by HDAC6 inhibition or by treatment with geniposide, a pharmacologically active component purified from gardenia fruit, resulted in reduced levels of ROS and Ca 2+ , and synaptic protection in multiple cellular and mouse models of AD (Choi et al, 2017; Guo et al, 2013; Lv et al, 2015; Reddy et al, 2012; Yu et al, 2016; Zhang et al, 2016a). Since mitochondrial trafficking inhibition in neurons is not specific to AD (De Vos and Hafezparast, 2017; Morfini et al, 2009; Trushina et al, 2004), the development of therapeutic strategies to restore axonal trafficking could be beneficial for multiple neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Targets deacetylated by HDAC6 include α-tubulin 4 , HSP90 5 , and cortactin 6 among others. 7,8 HDAC6 is involved in a diverse array of biological processes, including cell motility 9 , immune synapse formation 10 , viral infection 11 , and the degradation of misfolded proteins 12 , and has been associated with diseases. 13 In particular, HDAC6 recruits polyubiquitinated protein aggregates via its ZnF-UBD, and loads misfolded proteins onto dynein for microtubule-guided transport to the lysosome.…”
Section: Introductionmentioning
confidence: 99%